Cross-Sectional and Longitudinal Associations Among Weight Stigma, Psychological Distress, and Eating Behaviors in Youth with Obesity: A Clinical Sample - Wee Shen Khoo; Ying-Chu Chen; Yen-Yin Chou; Yu-Wen Pan; Yun-Han Weng; Meng-Che Tsai (Medicina)
Background and Objectives: Obesity in youth is a growing public health concern, placing them at higher risk for adverse physical and psychological outcomes. Understanding the predictors that affect weight management, particularly the role of internalized weight stigma, psychosocial factors, and eating behaviors, is essential for developing an effective intervention at longitudinal follow-up. Materials and Methods: We enrolled 102 youths with obesity aged 10 to 18 years old from clinical settings. Baseline demographic data, psychosocial measures, including the Weight Self-Stigma Questionnaire (WSSQ) and Hospital Anxiety and Depression Scale (HADS), and eating behavior scales, such as the Three-Factor Eating Questionnaire (TFEQ-R21) and eating disorder as Sick, Control, One, Fat, Food questionnaire (SCOFF), were collected in the first visit. We conducted a study with both cross-sectional and longitudinal components. Correlational bivariate analysis was conducted to explore relationships between key variables. The factors affecting BMI changes were investigated using generalized estimating equations (GEEs) as part of a longitudinal analysis. Results: The mean age of participants was 13.22 years and 63.7% were male. Bivariate correlation analysis revealed positive relationships between initial BMI Z-scores and WSSQ scores (r = 0.196, p < 0.05). In bivariate analysis, a negative correlation was found between the difference in BMI Z-scores and visit number (r = −0.428, p < 0.01). GEE analysis demonstrated that initial BMI Z-scores (coefficient = 1.342, p < 0.001) and anxiety (coefficient = 0.050, p < 0.001) were significant positive predictors of BMI Z-scores, while depression was negatively associated (coefficient = −0.081, p < 0.001). Excluding the TFEQ subscales, SCOFF improved the model’s QIC and highlighted WSSQ as a significant, albeit weak, predictor (p = 0.615 in the full model versus p < 0.05 in the reduced model). Conclusions: Psychosocial factors, particularly anxiety and weight stigma, are associated with elevated BMI Z-scores in youth affected by obesity in this study. The baseline age, BMI Z-score, internalized weight stigma, and psychological stress influenced the body weight trajectory over time. Frequent clinical follow-ups contribute to improved BMI outcomes. Future research may examine the efficacy of weight management by reducing weight stigma and psychological distress along with the outpatient care of obesity.